INFLUENCE OF EGO DEPLETION, SLEEP QUALITY, LIFESTYLE, INTERPERSONAL CONFLICT ON AUDITOR'S DECISION MAKING - Keumala Hayati; Paulina Ketaren; Nadia Siahaan (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Decision making is part of the work responsibilities of every employee, especially an auditor. This research was conducted to determine whether there is an influence between ego depletion , sleep quality , lifestyle , interpersonal conflict on the auditor 's decision making . The population in this research is 60 auditors who work and have their own KAP in Medan City. The age and working experience of the auditors ranged from 25 years old with an average of two years of working experience as an auditor. The sampling technique used in this study was purposive sampling. The data analysis technique uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Regression Analytical Test, T TEST and F TEST. Based on the results of research conducted, it shows that Ego Depletion and Interpersonal Conflict have a significant effect on Auditor Decision Making. While Lifestyle and Sleep Cycles do not show a significant influence on Decision Making by Auditors